Digital Technology Integration in Islamic Religious Education - Dhita Rizki Maulani; Nurul Latifatul Inayati (JIE (Journal of Islamic Education), 2026)
This study aims to examine the implementation of digital technology integration in the Islamic Religious Education learning process at the junior high school level. The method used is descriptive qualitative with a case study approach. Data were collected through structured interviews with two Islamic Religious Education teachers and six students in grades VII–IX, passive participant observation, and learning documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion. Data validity was strengthened through the use of triangulation techniques. The results show that digital technology integration is implemented systematically from the planning stage to the evaluation of learning. The learning process utilises various digital platforms, including Microsoft Word for assignment management, Google Classroom as a learning management system, e-modules or digital books as learning resources, and evaluative and interactive applications such as Wayground or Quizizz, Google Forms, and Computer-Based Test (CBT). The process of integrating technology and appropriate pedagogical strategies improves the quality of Islamic religious education. The technology-integrated learning has received a positive response from students. This is evident in their enthusiasm, active involvement, and ease in understanding the learning material. However, the implementation of digital technology integration still faces several obstacles, including teachers' limited time in developing digital learning content and students' misuse of technology during the learning process. Theoretically, this research contributes to strengthening the understanding of the practice of integrating digital technology into Islamic Religious Education learning in the junior high school context. Practically, the findings imply the need for more structured digital content planning and effective digital classroom management to ensure that technology utilisation aligns with learning objectives.